Fenomena Penggunaan Akun Pseudonym dalam Memenuhi Motif Identitas Pribadi pada Pengikut Autobase @karawangfess di Twitter - Tetty Kris Setiana Panjaitan; Yanti Tayo; Flori Mardiani Lubis (CHANNEL: Jurnal Komunikasi, 2020)
This research is motivated by the phenomenon of the use of pseudonym accounts that have appeared on Twitter, individual identities in the real world are different from those shown in cyberspace, identities tend to change and can be created. Each individual must have a personal identity motive that encourages them to use the account. Based on the description above, the identification of the research problem is how the phenomenon of using a Pseudonym account on Twitter fulfills the motives of personal identity for its users. So this research aims to find out and describe the phenomenon of using Pseudonym accounts in fulfilling the motives of a user's personal identity on Twitter. The research method used is descriptive qualitative to present descriptions and provide explanations objectively with data collection techniques through observation, interviews, and documentation. The focus of this research is based on personal identity motives. The results of the study explain that by using a Pseudonym account, users feel like they really are, they don't need to ignore people from the real world. Users can express themselves freely without being disturbed so that whatever behavior they do doesn't need to feel restricted because the identity built into the Pseudonym account will not let other people know who the person behind the Pseudoym account is.